Варіанти житлових будівель трипільської культури за елементами інтер’єру другого поверху - Черновол, Д.К. (Археологія і давня історія України, 2021)
У статті розглянуто варіанти житлових
споруд трипільської культури за елементами
інтер’єру другого поверху будівлі. Інтер’єр трипільських будівель досить стандартизований. Варіанти виділено за незначними змінами в інтер’єрі житлового приміщення будівлі. Загалом запропоновано п’ятнадцять варіантів житлових споруд. Варіанти розподілено у хронологічній послідовності залежно від їхньої появи. За виділеними
варіантами висловлено припущення щодо причини змін, які відбулися за час розвитку трипільської культури. Oven is a permanent element of interior of the
Trypillia culture house. An oven is always located to
the right from the entrance to the residential room of
the second storey. Other interior details, such as altar,
podium etc, are not met in every single house. This paper
aims to define variations of the Trypillia culture
houses according to the presence or lack of elements of
interior. Origin of variations is analyzed according to
the chronology of sites. The analysis is focused only on
the interior of the second storey.
Fifteen variations of Trypillia houses were defined
as of today. Variations one to three are typical only
for Early Trypillia. Those are different from the latter
variations by the location of an oven. Variations four
to six were formed during the Trypillia BI stage and
lasted till Trypillia CII. Other variations characterize
slight differences between certain periods of culture.
Organization of interior did not change much since
Trypillia BI. However Trypillia BI is characterized by
its highest variation.
The high level of unification of the Trypillia culture
dwellings was probably caused by the fact that the
house construction was the collective activity. Different
taboos, which did not let the deviation from commonly
accepted rules, also should not be excluded.
Certain individual elements could appear in the result
of house construction by an individual or family. They
could be also caused by the functioning of house and
some rational reasons.
Change in the location of an oven during Trypillia
BI could be explained by the climate change during
this period of time, which was noted by the number of
scholars, or incorporation of people from different cultural
units into Trypillia populations.